Kontekstualisasi Uzlah Di Tengah Masyarakat Modern - Jaenuri Jaenuri (Indonesia, 2023)
The purpose of this study is to analyze the concept of uzlah in the book of Kifayah al-Atqiya and then contextualize it in modern society. This type of research is library research with a Sufism approach. Data collection using documentation and interview methods. The primary source is the book of Kifayah al-Atqiya chapter uzlah. While the secondary data is in the form of books, journals and field data which have relevant studies as a support for the primary data. The findings of this study generally consist of two things; First, Uzlah is a human need that wants to get as close to Allah as possible and be safe from slander and environmental damage. Second, some uzlah practices in the midst of modern life such as Allah Conscious Prayers at the Patrap Surakarta hermitage, Meditation at the Darul Afkar Islamic boarding school and Suluk congregation of the Naqsyabandiyah congregation at the al-Manshur Islamic boarding school Popongan Klaten, Central Java.